Rapid eradication of vancomycin and methicillin-resistant Staphylococcus aureus by MDP1 antimicrobial peptide coated on photocrosslinkable chitosan hydrogel: in vitro antibacterial and in silico molecular docking studies - Ekhtiari-Sadegh, Sarvenaz; Samani, Saeed; Barneh, Farnoosh; Dashtbin, Shirin; Shokrgozar, Mohammad Ali; Pooshang Bagheri, Kamran (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Antibiotic resistance and weak bioavailability of antibiotics in the skin due to systemic administration leads to failure in eradication of vancomycin-and methicillin-resistant Staphylococcus aureus (VRSA and MRSA)-associated wound infections and subsequent septicemia and even death. Accordingly, this study aimed at designing a photocrosslinkable methacrylated chitosan (MECs) hydrogel coated by melittin-derived peptide 1 (MDP1) that integrated the antibacterial activity with the promising skin regenerative capacity of the hydrogel to eradicate bacteria by burst release strategy. The MECs was coated with MDP1 (MECs-MDP1), characterized, and the hydrogel-peptide interaction was evaluated by molecular docking. Antibacterial activities of MECs-MDP1 were evaluated against VRSA and MRSA bacteria and compared to MECs-vancomycin (MECs-vanco). Antibiofilm activity of MECs-MDP1 was studied by our novel 'in situ biofilm inhibition zone (IBIZ)' assay, and SEM. Biocompatibility with human dermal fibroblast cells (HDFs) was also evaluated. Results and Discussion: Molecular docking showed hydrogen bonds as the most interactions between MDP1 and MECs at a reasonable affinity. MECs-MDP1 eradicated the bacteria rapidly by burst release strategy whereas MECs-vanco failed to eradicate them at the same time intervals. Antibiofilm activity of MECs-MDP1 were also proved successfully. As a novel report, molecular docking analysis has demonstrated that MDP1 covers the structure of MECs and also binds to lysozyme with a reasonable affinity, which may explain the inhibition of lysozyme. MECs-MDP1 was also biocompatible with HDF skin cells, which indicates its safe future application. The antibacterial properties of a photocrosslinkable methacrylated chitosan-based hydrogel coated with MDP1 antimicrobial peptide were successfully proved against the most challenging antibiotic-resistant bacteria causing nosocomial wound infections; VRSA and MRSA. Molecular docking analysis revealed that MDP1 interacts with MECs mainly through hydrogen bonds with reasonable binding affinity. MECs-MDP1 hydrogels eradicated the planktonic state of bacteria by burst release of MDP1 in just a few hours whereas MECs-vanco failed to eradicate them. IBIZ assay showed the anti-biofilm activity of the MECs-MDP1 hydrogel too. These findings emphasize that MECs-MDP1 hydrogel would be suggested as a biocompatible wound-dressing candidate with considerable and rapid antibacterial activities to prevent/eradicate VRSA/MRSA bacterial wound infections.